Binding Say-on-Pay and Shareholder Value - Wagner, Alexander F; Wenk, Christoph (The Review of Corporate Finance Studies, 2026)
This paper investigates share price reactions and corporate responses to a set of policy changes regarding binding say-on-pay in Switzerland. The cross-section of stock price reactions indicates a trade-off: On the one hand, binding votes on executive compensation amounts, especially when conducted retrospectively, can help reduce agency costs by enhancing the alignment of management and shareholder interests. On the other hand, retrospective binding votes entail costs, for example, by distorting executives’ incentives for extracontractual, firm-specific investments. Corporate responses to the policy changes also reflect these trade-offs. Overall, our findings suggest that stronger and more direct shareholder power may not always be in the best interests of the shareholders themselves. (JEL G38, G34)